2016
DOI: 10.1038/nsmb.3174
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution 3D tomography of interactions and competition in the nuclear pore complex

Abstract: A selective barrier formed by intrinsically disordered Phe-Gly (FG) nucleoporins (Nups) allows transport receptor (TR)-facilitated translocation of signal-dependent cargos through the nuclear pore complexes (NPCs) of eukaryotic cells. However, the configuration of the FG-Nup barrier and its interactions with multiple TRs in native NPCs remain obscure. Here, we mapped the interaction sites of various TRs or FG segments within the FG-Nup barrier by using high-speed super-resolution microscopy and used these site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 46 publications
(81 reference statements)
4
91
2
Order By: Relevance
“…1 C-D). This map covers the majority of FG-domains of all native FG-Nups since this spatial distribution of the FG-domains agrees well with the full spectrum of the distribution of all FG-Nups in vivo obtained by SPEED microscopy [71][72][73][74][75] (Fig. 1).…”
Section: The Native Conformation Of the Fg-nups Barrier In The Npcssupporting
confidence: 83%
See 4 more Smart Citations
“…1 C-D). This map covers the majority of FG-domains of all native FG-Nups since this spatial distribution of the FG-domains agrees well with the full spectrum of the distribution of all FG-Nups in vivo obtained by SPEED microscopy [71][72][73][74][75] (Fig. 1).…”
Section: The Native Conformation Of the Fg-nups Barrier In The Npcssupporting
confidence: 83%
“…75 We found that these maps have fundamental similarities, suggesting that these different probes may largely bind to same groups of FG-domains or recognize almost all the available FG-domains in the native NPCs. Finally, a complete super-resolution 3D-map of the native configuration of FG-domains in the native NPCs was obtained by merging the above 3 integrated 3D-tomographies from all 3 sets 75 ( Fig. 1).…”
Section: The Native Conformation Of the Fg-nups Barrier In The Npcsmentioning
confidence: 76%
See 3 more Smart Citations